Portrait Of The Impact Of Broken Homes On Children's Psychology - Aulia Iswaratama; Casmini; Nurus Sa’adah (ASTEEC, 2024)
This study aims to examine the impact of broken home families on changes in children's personality. Because broken homes have an impact that can be an obstacle for children, especially in carrying out their daily lives. The method used in this research is through literature review. The results of the research found include explaining that basically the family has a big role in fostering and developing children's potential. However, when the family does not carry out its functions as it should, especially in broken home families, it greatly affects the mental and development of children, because broken home children are often alone and lack interaction.